Simple Laboratory Variables and Anthropometry as A Predictor Parameter For Visceral Fat Deposition - Ruslim, Daniel; Firmansyah, Yohanes; Santoso, Alexander Halim; Teguh, Stanislas Kotska Marvel Mayello; Mashadi, Fladys Jashinta; Lucius, Steven Hizkia (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Visceral fat, associated with increased risks of chronic diseases like cardiovascular disease and diabetes, plays a crucial role in metabolic health. Its proximity to vital organs allows it to release harmful cytokines and hormones. While CT and MRI are the gold standard for assessing visceral fat, their cost and accessibility limits their use, highlighting the need for alternative methods. This study investigates the potential of simple laboratory variables such as hemoglobin and anthropometric measurements containing BMI, body height, and muscle mass as predictors of visceral fat. This study aims to identify practical, cost-effective tools for monitoring visceral fat, supporting disease prevention and management, particularly in limited resources settings. This study was conducted at St. Assisi Church with 32 respondents. Statistical analysis applies multiple linear regression to examine the relationship between anthropometric measurements, laboratory variables, and visceral fat. The multiple linear regression analysis identifies hemoglobin, body weight, body height, body fat, and arm total muscle as significant predictors of the dependent variable. Hemoglobin, body height, body fat, and arm total muscle show negative associations, while body weight positively predicts the outcome. These findings highlight the critical roles of these variables in influencing the dependent variable. This study identifies hemoglobin, body weight, height, fat, and arm muscle as significant predictors, highlighting muscle's critical role in functionality.